Numerical simulation of the magnetoresistance effect controlled by electric field in p-n junction - 铴盼 谌文杰 王娇 闫兆文 乔坚栗 肖彤 王欣 庞正鹏 杨建红 (Chinese physics B, 2016)
The magnetoresistance effect of a p-n junction under an electric field which is introduced by the gate voltage at room temperature is investigated by simulation. As auxiliary models, the Lombardi CVT model and carrier generation- recombination model are introduced into a drift-diffusion transport model and carrier continuity equations. All the equa- tions are discretized by the finite-difference method and the box integration method and then solved by Newton iteration. Taking advantage of those models and methods, an abrupt junction with uniform doping is studied systematically, and the magnetoresistance as a function of doping concentration, SiO2 thickness and geometrical size is also investigated. The simulation results show that the magnetoresistance （MR） can be controlled substantially by the gate and is dependent on the polarity of the magnetic field.